THE EUROPEAN UNION’S TRADE NEGOTIATIONS WITH THE ACP:ENTRAPPED BY ITS OWN RHETORICAL STRATEGY? - Lotte Drieghe (Romanian Journal of European Affairs, 2008)
This paper deals with the Economic Partnership Agreements (EPAs) between the European Union (EU) and the group of African, Caribbean and Pacific (ACP) countries. It addresses the question why the EU firmly insisted on upholding the negotiating deadline for these new trade agreements, despite the very damaging consequences; these hastily initialed trade deals entailed. Regional integration in the South was hampered; the development of the friendly image of the EU got a serious blow; the EU did not manage to include the WTO plus issues, and the prospect of full EPAs at later stage is not guaranteed. We first qualify the Union’s argument to the expiry of a waiver by the World Trade Organization (WTO), which legitimized the former trade regime, and placed an external and insurmountable pressure on the negotiations. There is no rational explanation for Europe’s harsh attitude on the EPA deadline, since neither legal, nor economic interests would have been harmed, if the deadline had been postponed. The main argument advanced in this article addresses whether the EU had to push through these trade deals, because it had entrapped itself through its own ‘rhetorical action’. In its negotiation discourse, the European Commission (EC) had so often emphasized the deadline together with the fact that there were no alternatives to EPAs, that it could not change its mind overnight, when at the end of the 2007 negotiations they were still going nowhere. The Union was forced to keep up with the deadline it had imposed upon itself with the risk of losing all its credibility.